SUSANA FIORITO AND THE ARCHIVE OF CORDOBAZOS, CLASSISM AND THE NEW LEFT - Celentano, Adrian (Revista de Historia Social y de las Mentalidades, 2020)
The archival and editorial practices of Susana Fiorito, historian and militant of the new intellectual left, constituted since 1970 the materials of the “Archivos del Sindicato de Trabajadores de Concord”. In this article we are studied the role of Fiorito in the preservation of these materials, identifying his interpretation of the history of the working class protagonist of the “Cordobazos”, and analizying in the organization of the archive the register of divergences among intellectuals about the relationship of the “clasistas” workers militancy with the political organizations of the new left.
Keywords: Archive; Intellectuals; Classism; New Left